A lightweight heat-insulating diatomite thermal insulation board and preparation method thereof
Through the preparation method of thermal insulation boards integrating diatomaceous earth, silica aerogel and microencapsulated phase change materials, the existing thermal insulation materials have been solved, and the combination of lightweight and efficient heat insulation is achieved.
Patent Information
- Application Number
- CN202410815204.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-06-24
AI Technical Summary
Existing thermal insulation materials have problems such as large weight, high cost, easy damage and limited thermal regulation performance, making it difficult to achieve both lightweight and efficient thermal insulation.
The thermal insulation board preparation method is adopted to integrate diatomaceous earth, silica aerogel and microencapsulated phase change materials. Cellulose glue is used as a binder to combine metal oxide nanoparticles, aluminum hydroxide and calcium carbonate to form a highly efficient thermal insulation board.
The low thermal conductivity and excellent thermal regulation performance of lightweight thermal insulation sheets are achieved, which reduces the overall structural weight, improves thermal insulation performance and physical stability, and controls the preparation cost.
Smart Images

Figure BDA0004907378690000091 
Figure BDA0004907378690000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation boards, and in particular to a lightweight thermal insulation diatomite thermal insulation board and a preparation method thereof. Background Art
[0002] In modern construction and industrial applications, the demand for thermal insulation materials is growing, especially in the pursuit of energy efficiency and environmental sustainability. Traditional thermal insulation materials such as foam plastics, mineral fibers and expanded polystyrene, although excellent in thermal insulation, often have problems such as heavy weight, flammability and large environmental impact. With the development of technology, lightweight and efficient thermal insulation materials have become a hot topic of research. In recent years, diatomaceous earth has been widely studied as a thermal insulation material due to its natural pore structure and low thermal conductivity. At the same time, as an ultra-light material, silica aerogel has extremely low thermal conductivity, which makes it show great potential in the fields of aerospace and building insulation. In addition, phase change materials (PCM) are also gradually used in thermal insulation materials to improve thermal regulation performance because they can absorb or release a large amount of heat energy when the temperature changes.
[0003] Although the application of diatomaceous earth and silica aerogel in thermal insulation materials has gradually increased, they still face some technical challenges when used alone. Diatomaceous earth has low mechanical strength and is easy to break, which limits its use in applications that need to withstand certain mechanical loads. Although silica aerogel has excellent thermal insulation properties, its high cost and brittleness limit its large-scale application. In addition, although current phase change materials can provide excellent thermal regulation capabilities, they often face leakage risks in practical applications due to insufficient packaging technology, and compatibility with other materials is also a major challenge. Therefore, although these materials each have certain thermal insulation advantages, how to effectively combine them while overcoming their respective shortcomings to achieve a new type of thermal insulation material that is both lightweight and has efficient thermal insulation properties is still a technical problem.
[0004] The present invention aims to solve the problems existing in the prior art, such as the heavy weight, high cost, easy damage and limited thermal regulation performance of thermal insulation materials. In particular, the invention requires the development of an insulation board that integrates diatomaceous earth, silica aerogel and microencapsulated phase change material. The board should not only have the characteristics of light weight, but also have excellent thermal insulation effect and good physical stability. In addition, the insulation board should be able to achieve effective cost control during the preparation process, as well as good industrial applicability, including easy processing and molding and good environmental adaptability, which is crucial for commercial applications. Solving these technical problems will be able to promote the advancement of insulation material technology and meet the high standards of modern construction and industry. Summary of the invention
[0005] In order to achieve the above-mentioned purpose of the invention and to solve the above-mentioned technical problems, the present invention provides a lightweight heat-insulating diatomite insulation board and a preparation method thereof. The specific scheme is as follows:
[0006] A method for preparing a lightweight heat-insulating diatomite thermal insulation board, the method comprising the following steps:
[0007] A1 dissolves cellulose gum in water to form a solution;
[0008] A2: diatomaceous earth powder, silica aerogel powder, metal oxide nanoparticles, aluminum hydroxide, tributyrin and calcium carbonate are mixed for 10 minutes, microencapsulated phase change material (PCM) is gradually added and stirring is continued for 20 minutes, and then the cellulose gum solution of step A1 is added and stirred to mix;
[0009] A3: placing the mixture obtained in step A2 into a mold, compacting and drying the mixture to obtain a plate;
[0010] A4: coating the plate obtained in step A3 with the silica aerogel solution and curing it.
[0011] Preferably, the microencapsulated phase change material (PCM) is prepared by the following method:
[0012] B1: paraffin wax and xylene are mixed in a mass ratio of 1:1-1:2, heated until the paraffin wax is completely dissolved, and then polymethyl methacrylate (PMMA) and an initiator accounting for 5%-15% of the mass of the paraffin wax are added, and stirred continuously at 80°C to fully blend;
[0013] B2 nanoclay is premixed with epoxy resin in a mass ratio of 1:2-1:4, and added to the mixture of paraffin and PMMA, and stirred until evenly distributed;
[0014] B3: continuing to heat the mixture of step B2 at 80° C. and stirring the mixture, while gradually adding diethylenetriamine having an epoxy resin content of 30%, maintaining the temperature and stirring for 2 hours to form a polymer shell;
[0015] B4: Cool the mixture of step B3 to room temperature, filter and wash to remove unreacted monomers and solvent to form microcapsules, filter and wash the microcapsules, and dry.
[0016] Preferably, the initiator is azobisisobutyronitrile (AI BN), and the amount used is 0.5-2% of the mass of the paraffin.
[0017] Preferably, the melting point of the paraffin wax is 21-23°C.
[0018] Preferably, the diatomaceous earth powder has a particle size of 200-500 microns, the silica aerogel powder has a thermal conductivity of about 0.015 W / m·K and a particle size of 100-300 microns, and the metal oxide nanoparticles are selected from aluminum oxide or zinc oxide and have a particle size of 100 nanometers.
[0019] Preferably, the molding conditions of step A3 are: compacting at a pressure of 150 bar for 30 minutes at 25° C., and the drying conditions are drying in an oven at 60° C. for 12 hours.
[0020] Preferably, the concentration of the cellulose gum solution is 2-5%.
[0021] Preferably, the diatomaceous earth powder comprises 55-60 parts, silica aerogel powder comprises 10-15 parts, metal oxide nanoparticles comprises 3-5 parts, aluminum hydroxide comprises 3-5 parts, tributyrin comprises 2-4 parts, calcium carbonate comprises 5-10 parts, and microencapsulated phase change material (PCM) comprises 5-10 parts.
[0022] Preferably, in step A4, a 0.5 mm thick 5% concentration silica aerogel solution is coated and cured at room temperature for 24 hours.
[0023] The invention also provides a lightweight heat-insulating diatomaceous earth thermal insulation board, which is prepared by the preparation method.
[0024] The microencapsulated phase change material (PCM) used in the present invention forms stable microcapsules through the chemical combination of paraffin wax and polymethyl methacrylate (PMMA). These microcapsules can absorb or release heat when the ambient temperature changes, achieving dynamic thermal regulation. This technology improves the thermal storage capacity of the insulation board, enhancing its responsiveness to temperature fluctuations and thermal stability.
[0025] By utilizing the low thermal conductivity of silica aerogel, the present invention forms an efficient thermal insulation layer on the surface of the thermal insulation board. The application of this material not only improves the thermal insulation performance, but also helps reduce the weight of the overall structure due to its lightweight characteristics.
[0026] The introduction of microencapsulated PCM optimizes the thermal insulation effect of the board at different temperatures, enabling it to effectively cope with changes in ambient temperature, while the addition of silica aerogel further reduces thermal conduction and enhances the thermal insulation effect. The combination of these two materials provides a lightweight and efficient thermal insulation solution.
[0027] In the present invention, diatomaceous earth and silica aerogel provide good thermal insulation properties and lightweight structure for the base materials. The addition of microencapsulated PCM brings new functions of dynamic thermal management to these traditional materials. Cellulose gum, as a binder, ensures the uniformity of the mixture and the mechanical stability after molding, thereby achieving the optimization of the overall technical solution and improving the performance.
[0028] The beneficial effects brought by the technical solution provided by the present invention are:
[0029] Enhanced thermal regulation: The invention significantly optimizes the thermal storage and release capabilities of the insulation board by introducing microencapsulated phase change materials (PCMs). This material absorbs or releases heat when the temperature changes, effectively regulating the temperature of the internal environment, achieving continuous temperature control and improving thermal comfort.
[0030] Realization of low thermal conductivity: By utilizing the extremely low thermal conductivity of silica aerogel and combining it with the good thermal insulation properties of diatomaceous earth, the present invention provides an insulation board with extremely low heat transfer rate, which effectively blocks heat flow and improves the thermal insulation performance of the overall structure.
[0031] Lightweight materials: By using two lightweight materials, diatomaceous earth and silica aerogel, the present invention significantly reduces the overall weight of the insulation board. Both diatomaceous earth and silica aerogel are known for their low density, which not only reduces the burden on the structure. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0033] Example 1
[0034] A lightweight heat-insulating diatomite thermal insulation board, the implementation steps are as follows:
[0035] Diatomaceous earth powder: 58 parts, particle size 300 microns;
[0036] Silica aerogel powder: 12 parts, particle size 200 microns, thermal conductivity 0.015 W / m·K;
[0037] Microencapsulated phase change material (PCM): 7 parts, prepared by the following steps:
[0038] Paraffin wax (melting point 22°C) and xylene were mixed in a mass ratio of 1:2 and heated until the paraffin wax was completely dissolved.
[0039] To the mixture were added 10% of polymethyl methacrylate (PMMA) and 1% of initiator azobisisobutyronitrile (AI BN) based on the mass of the paraffin wax.
[0040] Stirring was continued at 80°C for 2 hours to form a polymer shell.
[0041] The mixture was cooled to room temperature, filtered and washed to remove unreacted monomers and solvent, and finally dried to obtain microcapsules.
[0042] Metal oxide nanoparticles are aluminum oxide, 100 nanometers: 4 parts
[0043] Aluminum hydroxide: 4 parts
[0044] Tributyrin: 3 parts
[0045] Calcium carbonate: 7 parts
[0046] Cellulose gum: 3 parts, dissolved in water to form a 4% solution
[0047] Preparation steps
[0048] Preparation of cellulose gum solution:
[0049] The cellulose gum is dissolved in water to form a cellulose gum solution.
[0050] Mixing and stirring:
[0051] Add diatomaceous earth powder, silica aerogel powder, metal oxide nanoparticles, aluminum hydroxide, tributyrin and calcium carbonate into a container and stir for 10 minutes.
[0052] The prepared microencapsulated PCM was gradually added and stirring was continued for 20 minutes.
[0053] Add cellulose gum solution and stir until well mixed.
[0054] Forming and curing:
[0055] The mixture was transferred into a mould and compacted at 25°C for 30 minutes using a pressure of 150 bar.
[0056] The compacted board was placed in an oven at 60°C and dried for 12 hours.
[0057] Surface treatment:
[0058] The dried plate was evenly coated with a 0.5 mm thick layer of 5% silica aerogel solution.
[0059] Cure at room temperature for 24 hours.
[0060] Example 2
[0061] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the amount of the microencapsulated phase change material was 5 parts.
[0062] Example 3
[0063] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the amount of the microencapsulated phase change material was 10 parts.
[0064] Example 4
[0065] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that 5% of the mass of the paraffin wax was added with polymethyl methacrylate (PMMA).
[0066] Example 5
[0067] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that polymethyl methacrylate (PMMA) accounting for 15% of the mass of the paraffin was added.
[0068] Example 6
[0069] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that an initiator azobisisobutyronitrile (AI BN) was added in an amount of 0.5% of the mass of the paraffin.
[0070] Example 7
[0071] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that an initiator azobisisobutyronitrile (AI BN) was added in an amount of 2% of the mass of the paraffin.
[0072] Example 8
[0073] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the concentration of the cellulose gum solution was 2%.
[0074] Example 9
[0075] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the concentration of the cellulose gum solution was 5%.
[0076] Example 10
[0077] The thermal insulation board is prepared according to the same preparation method as in Example 1, except that the metal oxide nanoparticles are selected from zinc oxide.
[0078] Embodiment 11
[0079] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the particle size of the silica aerogel powder was 100 μm.
[0080] Example 12
[0081] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the particle size of the silica aerogel powder was 300 μm.
[0082] Example 13
[0083] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the nanoclay and the epoxy resin were premixed in a mass ratio of 1:2.
[0084] Embodiment 14
[0085] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the nanoclay and the epoxy resin were premixed in a mass ratio of 1:4.
[0086] Embodiment 15
[0087] A lightweight heat-insulating diatomite thermal insulation board, the implementation steps are as follows:
[0088] Diatomaceous earth powder: 55 parts, particle size 200 microns;
[0089] Silica aerogel powder: 10 parts, particle size 100 microns, thermal conductivity 0.015 W / m·K;
[0090] Microencapsulated phase change material (PCM): 5 parts, prepared by the following steps:
[0091] Paraffin wax (melting point 21°C) and xylene were mixed in a mass ratio of 1:1 and heated until the paraffin wax was completely dissolved.
[0092] 5% of polymethyl methacrylate (PMMA) and 0.5% of initiator azobisisobutyronitrile (AI BN) were added to the mixture, based on the mass of the paraffin.
[0093] Stirring was continued at 80°C for 2 hours to form a polymer shell.
[0094] The mixture was cooled to room temperature, filtered and washed to remove unreacted monomers and solvent, and finally dried to obtain microcapsules.
[0095] Metal oxide nanoparticles 100 nanometers: 3 parts (aluminum oxide)
[0096] Aluminum hydroxide: 3 parts
[0097] Tributyrin: 2 parts
[0098] Calcium carbonate: 5 parts
[0099] Cellulose gum: 2%, dissolved in water to form a solution
[0100] Preparation steps
[0101] Preparation of cellulose gum solution:
[0102] The cellulose gum is dissolved in water to form a cellulose gum solution.
[0103] Mixing and stirring:
[0104] Add diatomaceous earth powder, silica aerogel powder, metal oxide nanoparticles, aluminum hydroxide, tributyrin and calcium carbonate into a container and stir for 10 minutes.
[0105] The prepared microencapsulated PCM was gradually added and stirring was continued for 20 minutes.
[0106] Add cellulose gum solution and stir until well mixed.
[0107] Forming and curing:
[0108] The mixture was transferred into a mould and compacted at 25°C for 30 minutes using a pressure of 150 bar.
[0109] The compacted board was placed in an oven at 60°C and dried for 12 hours.
[0110] Surface treatment:
[0111] The dried plate was evenly coated with a 0.5 mm thick layer of 5% silica aerogel solution.
[0112] Cure at room temperature for 24 hours.
[0113] Example 16
[0114] A lightweight heat-insulating diatomite thermal insulation board, the implementation steps are as follows:
[0115] Diatomaceous earth powder: 60 parts, particle size 500 microns;
[0116] Silica aerogel powder: 15 parts, particle size 300 microns, thermal conductivity 0.015 W / m·K;
[0117] Microencapsulated phase change material (PCM): 10 parts, prepared by the following steps:
[0118] Paraffin wax (melting point 23°C) and xylene are mixed in a mass ratio of 1:2 and heated until the paraffin wax is completely dissolved.
[0119] 15% of polymethyl methacrylate (PMMA) and 2% of initiator azobisisobutyronitrile (AI BN) were added to the mixture based on the mass of the paraffin.
[0120] Stirring was continued at 80°C for 2 hours to form a polymer shell.
[0121] The mixture was cooled to room temperature, filtered and washed to remove unreacted monomers and solvent, and finally dried to obtain microcapsules.
[0122] Metal oxide nanoparticles 100 nanometers: 5 parts (aluminum oxide)
[0123] Aluminum hydroxide: 5 parts
[0124] Tributyrin: 4 parts
[0125] Calcium carbonate: 10 parts
[0126] Cellulose gum: 5%, dissolved in water to form a solution
[0127] Preparation steps
[0128] Preparation of cellulose gum solution:
[0129] The cellulose gum is dissolved in water to form a cellulose gum solution.
[0130] Mixing and stirring:
[0131] Add diatomaceous earth powder, silica aerogel powder, metal oxide nanoparticles, aluminum hydroxide, tributyrin and calcium carbonate into a container and stir for 10 minutes.
[0132] The prepared microencapsulated PCM was gradually added and stirring was continued for 20 minutes.
[0133] Add cellulose gum solution and stir until well mixed.
[0134] Forming and curing:
[0135] The mixture was transferred into a mould and compacted at 25°C for 30 minutes using a pressure of 150 bar.
[0136] The compacted board was placed in an oven at 60°C and dried for 12 hours.
[0137] Surface treatment:
[0138] The dried plate was evenly coated with a 0.5 mm thick layer of 5% silica aerogel solution.
[0139] Cure at room temperature for 24 hours.
[0140] Comparative Example 1
[0141] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the microencapsulated phase change material (PCM) was missing.
[0142] Comparative Example 2
[0143] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the nano-alumina particles were missing.
[0144] Comparative Example 3
[0145] The thermal insulation board was prepared according to the same preparation method as in Example 1, except that the silica aerogel powder was absent.
[0146] Comparative Example 4
[0147] The thermal insulation board is prepared according to the same preparation method as in Example 1, except that the surface spraying step is omitted.
[0148] Experimental test:
[0149] 1. Thermal conductivity test
[0150] Refer to GB / T 10294-2008 "Determination of thermal resistance and related properties of solid materials under steady-state conditions".
[0151] Test conditions: The thermal conductivity of the sample was measured using a heat flow meter method. The test temperature was 25°C and a constant temperature environment was maintained.
[0152] 2. Thermal insulation performance test
[0153] Test steps:
[0154] Use the sample material to build two sealed boxes of the same size; place a temperature recorder in each box;
[0155] The external environment temperature gradually rises, and the internal temperature changes are recorded; the difference in the internal temperature of the two boxes is compared;
[0156] Starting temperature: 20°C (room temperature);
[0157] Target maximum temperature: 50°C (simulating high temperature environment);
[0158] Temperature increase rate: 5°C per hour until the maximum temperature is reached.
[0159] Table 1 Thermal conductivity test
[0160]
[0161]
[0162] Example 1 exhibits the lowest thermal conductivity, confirming the design's leading position in providing excellent thermal insulation. This effect is mainly due to the highly effective thermal insulation combination of diatomaceous earth and silica aerogel and the optimized ratio of microencapsulated phase change material (PCM). This combination not only reduces the heat transfer rate, but also enhances the thermal regulation properties of the material, which can absorb or release heat when the temperature changes, thereby maintaining the stability of the internal environment.
[0163] Comparative Examples 1 to 4 show higher thermal conductivity, especially in Comparative Example 4, where the lack of key components such as PCM or aerogel leads to a significant decrease in its thermal insulation performance. These comparative examples effectively demonstrate the important role of microencapsulated phase change materials and silica aerogel in improving thermal insulation effects.
[0164] The remaining embodiments show that the thermal conductivity fluctuates to a certain extent with the change of the PCM ratio or the adjustment of other components. This shows that the fine-tuning of other embodiments can also provide appropriate performance adjustment according to specific application requirements, showing the design flexibility and wide application potential of the present invention.
[0165] Table 2 Thermal insulation performance test
[0166] Test No. Final internal temperature ℃ Temperature difference ℃ Example 1 25 25 Example 2 27 23 Example 3 26 24 Example 4 29 21 Example 5 30 20 Example 6 28 22 Example 7 32 18 Example 8 31 19 Example 9 33 17 Example 10 34 16 Embodiment 11 36 14 Example 12 38 12 Comparative Example 1 40 10 Comparative Example 2 42 8 Comparative Example 3 44 6 Comparative Example 4 46 4
[0167] Example 1 exhibits the best thermal insulation performance due to its use of microencapsulated phase change material (PCM), silica aerogel, and other insulation-enhancing ingredients such as cellulose gum and metal oxide nanoparticles. PCM is particularly helpful in absorbing and releasing heat, which is particularly critical in high temperature conditions because it can effectively control temperature changes.
[0168] Examples 2 to 12 show the thermal insulation performance under different configurations, where gradually increasing or changing the material combination leads to a gradual reduction in the temperature difference. In particular, Example 3 (more PCM) and Example 5 (higher concentration of PMMA) still show good thermal insulation performance.
[0169] Comparative Examples 1 to 4 successively removed or replaced key thermal insulation components, showing a significant decrease in thermal insulation performance.
[0170] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a lightweight heat-insulating diatomite thermal insulation board, characterized in that: The preparation method comprises the following steps: A1 dissolves cellulose gum in water to form a solution; A2: 55-60 parts of diatomaceous earth powder, 10-15 parts of silica aerogel powder, 3-5 parts of metal oxide nanoparticles, 3-5 parts of aluminum hydroxide, 2-4 parts of tributyrin and 5-10 parts of calcium carbonate are mixed, 5-10 parts of microencapsulated phase change material (PCM) are gradually added and stirred continuously, and then the cellulose gum solution of step A1 is added and stirred and mixed uniformly, wherein the metal oxide nanoparticles are selected from aluminum oxide or zinc oxide; A3: placing the mixture obtained in step A2 into a mold, compacting and drying the mixture to obtain a plate; A4: coating the plate obtained in step A3 with the silica aerogel solution and curing it. The microencapsulated phase change material (PCM) is prepared by the following method: B1: paraffin wax and xylene are mixed in a mass ratio of 1:1-1:2, heated until the paraffin wax is completely dissolved, and then polymethyl methacrylate (PMMA) and an initiator accounting for 5%-15% of the mass of the paraffin wax are added, and stirred continuously to fully blend. The initiator is azobisisobutyronitrile (AIBN), and the amount used is 0.5-2% of the mass of the paraffin wax; B2 nanoclay is premixed with epoxy resin in a mass ratio of 1:2-1:4, and added to the mixture of paraffin and PMMA, and stirred until evenly distributed; B3: continue to heat the mixture of step B2 and stir the mixture, and gradually add diethylenetriamine with an epoxy resin content of 30%, maintain the temperature and stir, to form a polymer shell; B4: Cool the mixture of step B3 to room temperature, filter and wash to remove unreacted monomers and solvent to form microcapsules, filter and wash the microcapsules, and dry.
2. The preparation method according to claim 1, characterized in that: The particle size of the diatomaceous earth powder is 200-500 microns.
3. The preparation method according to claim 1, characterized in that: The thermal conductivity of the silicon dioxide aerogel powder is 0.015 W / m·K, and the particle size is 100-300 microns.
4. The preparation method according to claim 1, characterized in that: The molding conditions of step A3 are: compaction at 150 bar pressure for 30 minutes at 25°C, and drying conditions are drying in an oven at 60°C for 12 hours.
5. The preparation method according to claim 1, characterized in that: The concentration of the cellulose gum solution is 2-5%.
6. A lightweight heat-insulating diatomite insulation board, characterized in that: The plate is prepared by the method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Phase-change thermal insulation material and preparation method and application thereof
CN111454694A
Processing technology for reducing crack generation rate in sintering process of diatomite insulating bricks
CN112279631A